Penghormatan Al-Qur'an Terhadap Perempuan dengan Narasi Metaforis: Studi atas Q.S. al-Baqarah [2]: 223 - Mahbub Ghozali; Nur Afni Khafsoh (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
This study discusses the use of the poetic narrative of the Qur'an in mentioning the sexual relations between men and women mentioned in Q.S. Al-Baqarah [2]: 223. This verse is often used to show women as male sexual objects in the satisfaction of their sexual desires. The defense of this argument always argues for the meaning contained, not in the message contained with the poetic narrative in it. This study uses a qualitative method with a type of literature study. As for analyzing the data, this study uses content analysis. This study concludes that the poetic narrative in Isti'arah, majāz, and tasbih aims to give glory to women and respect their position. Using this form, the content of the resulting meaning refers to the sexual function aimed at obtaining offspring so that everything related to it is done to achieve that goal. The poetic narrative also contains an emphasis on treating women with the same model and form as the Qur'an treats them. Discovering the relationship of language and message contained in the poetic narrative on the subject of women can provide a new perspective in understanding the position of women in their social sphere. Women are beautiful creatures who should be treated with respect as the Qur'an treats them poetically